Count the ways : a novel - Maynard, Joyce, 1953- (William Morrow, an imprint of HarperCollinsPublishers, 2021)
"In her most ambitious novel to date, New York Times bestselling author Joyce Maynard takes on the topography of the heart - a landscape of grief, reconciliation, forgiveness, and the way the mistakes of parents are passed down through generations, to fester, or to be healed"--